Pencegahan Bullying Oleh Tim KKN UNNES Giat 8 Di SD Negeri Rowoboni 02 - Novia, Diah; Arfiana, Alif (Universitas Negeri Semarang, 2025)
Bullying Behavior in children's environment is very disturbing to parents, society, and especially schools. Schools as a place for children's formal education are places that are very vulnerable to incidents of bullying. The aim of this community service activity is to educate about the dangers of bullying behavior in elementary school children. The methods used in service are socialization and training. In its implementation, the service team understands the dangers of bullying which can disrupt an individual's mental health and self-confidence. Next, we carry out a simulation session between one friend and another so that the condition of each child is known. The results of the activity showed that the children were able to convey their experiences and complaints, resulting in individual openness. This activity also succeeded in increasing awareness of one's own existence, building empathy and support for one another. With this activity, it is hoped that it can reduce bullying behavior in schools and also in their respective living environments.